Is Length of Stay Influenced by the Weekday On Which Lumbar Surgery is Performed. Issue 7 (16th November 2020) - Sivaganesan, Ahilan; Devin, Clinton J; Khan, Inamullah; Kerezoudis, Panagiotis; Nian, Hui; Harrell, Frank E; Bydon, Mohamad; Asher, Anthony L
Graphical Abstract: